Investments in Electro Mobility for Freight Traffics in the Field of City Logistics: A Profitability Analysis - Sabrina Gries; Christian Witte; René Föhring; Stephan Zelewski (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Electro mobility is considered to be a pioneering trend in the field of road traffic to reduce the emissions of greenhouse gases. Because of technical restrictions, which limit the range and loading capacity of vehicles, electro mobility is mostly discussed with regard to passenger cars. However, recent developments raise the question whether electro mobility can be also used promisingly for local freight traffics of the so-called "city logistics". Interesting are especially transports on the "first" and "last mile" of supply chains with combined transports. However, electro mobility has only then potential as a future trend if the profitability of investments can be demonstrated. The profitability of investments in electro mobility is being examined. The costs of three diesel versus three similar electric commercial vehicles are calculated for a typical case of application in city logistics. The analyses cover three scenarios that represent alternative investment options for the application of electro mobility: the complete purchase of electric commercial vehicles, the partial purchase combined with renting the battery as well as the complete vehicle leasing. Drive-specific features like e.g. the smaller range of electric commercial vehicles compared to diesel commercial vehicles are especially considered. It is shown that already today the regarded electric commercial vehicles prove to be economically attractive in some of the examined scenarios. Moreover, it is elucidated which expectable changes in future within the circumstances of city logistics will promote investments in electro mobility.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; city logistics; electro mobility; freight traffic; profitability analysis